The Evaluation of Potential Cytotoxic Effect of Different Proton Pump Inhibitors on Different Human Cancer Cell Lines - Qasem, Aya; Kasabri, Violet; AbuRish, Eman; Bustanji, Yasser; Al-Hiari, Yusuf; Al-Abbasi, Reem; Abu-Irmaileh, Bashaer; Alalawi, Sundus (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Objective: To assess the differential cytotoxic activity of PPIs on different human cancer cell lines; namely A549 lung cancer, CACO-2 colorectal cancer, MCF-7 breast cancer, and PANC-1 pancreatic cancer, A375 skin melanoma. Methods: In this study, the five human cancer cell lines and human non-cancerous fibroblasts were treated with increasing concentration of PPIs Omeprazole (OMP), Esomeprazole (ESOM), and Lansoprazole (LANSO) (50-300μM), over 24h, 48h, and 72h. Cell viability was determined using 3-(4,5- Dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay and the IC50 values of PPIs were measured. The most sensitive cell line A375 was used for further investigation. The cytotoxic effects of LANSO on these cells were assessed using Annexin-V Propidium Iodide (AV-PI) flow cytometry. As of action mechanism; anti-inflammatory effects of each PPIs and PPIs-DOXO combination therapy on LPS-stimulated RAW 264.7 mouse macrophages were assessed. Results: Dose and time dependence cytotoxic activity of PPIs on human cancer cell lines was founded. Unlike DOXO; All PPIs had a selective cytotoxic effect in the normal fibroblasts. Unlike the equipotent OMP and ESOM; LANSO was the most potent drug with IC50 values at 72h of 99, 217, 272, 208, 181μM against A375, A549, CACO-2, MCF-7, and PANC-1, respectively. AV-PI flow cytometry revealed dose-dependent apoptotic effects of LANSO alone and substantially enhanced in DOXO-co-treatments. Interestingly unlike ESOM and OMP, LANSO proved more effective than indomethacin in LPS-stimulated RAW 264.7 macrophages. None of the tested compounds, as well as indomethacin, exerted any cytotoxicity against RAW 264.7 macrophages. PPIs-DOXO lacked potential synergistic combination antiinflammation therapies. Conclusion: This study provides the evidence that PPIs induce a direct and differential cytotoxic activity against human cancer cell line by the induction of the apoptosis. Moreover, PPIs increase cancer cell lines sensitivity to doxorubicin via apoptosis augmentation. Nevertheless, PPIs-DOXO lacked potential synergistic combination therapies in either antiproliferation or anti-inflammation.
Keywords: apoptosis and Annexin-V propidium iodide